The Implementation of Discovery Learning to Teach Speaking at the First Grade Students at SMP Institut Indonesia - Irmayanti Mufida; Gusti Nur Hafifah; Linda Mayasari (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2015)
The result of this study show that the English teacher synchronized the steps of scientific approach in Curriculum 2013 with the applications of Discovery Learning in his lesson plan. The steps are observing through stimulation, questioning through problem statement, experimenting through collecting data, associating through processing data, communicating through verification and generalization. They make them, the students become more active in oral activities and all of activities can make the students do not feel bored. This study also attempts to know about the student's responses after the implementation of Discovery Learning. It can be concluded that the students more understand easily toward the materials which were taught, especially in their speaking skill because Discovery Learning has given positive impact for the students. Finally the researcher suggested that the teachers should always give the motivation and provide the other materials using the creative techniques so that the learning process can more effective and meaningful. It means that the students will never forget their experiences and the teacher's explanations within a long period.